Association between Anxiety Levels and Weight Change in the Multiethnic Study of Atherosclerosis. (8th October 2014) - Rieke, Katherine; Durazo-Arvizu, Ramon; Liu, Kiang; Michos, Erin D.; Luke, Amy; Kramer, Holly
Abstract : Objective . To examine the association between anxiety and weight change in a multiethnic cohort followed for approximately 10 years. Methods . The study population consisted of participants of the multiethnic study of atherosclerosis who met specified inclusion criteria ( n = 5, 799). Weight was measured at baseline and four subsequent follow-up exams. Anxiety was analyzed as sex-specific anxiety quartiles (QANX). The relationship between anxiety level and weight change was examined using a mixed-effect model with weight as the dependent variable, anxiety and time as the independent variables, and adjusted for covariates. Results . Average annual weight change (range) was −0.17 kg (−6.04 to 4.38 kg) for QANX 1 (lowest anxiety), −0.16 kg (−10.71 to 4.45 kg) for QANX 2, −0.15 kg (−8.69 to 6.39 kg) for QANX 3, and −0.20 kg (−7.12 to 3.95 kg) for QANX 4 (highest anxiety). No significant association was noted between QANX and weight change. However, the highest QANX was associated with a −2.48 kg (95% CI = −3.65, −1.31) lower baseline weight compared to the lowest QANX after adjustment for all covariates. Conclusions . Among adults, age 45–84, higher levels of anxiety, defined by the STPI trait anxiety scale, are associated with lower average baseline weight but not with weight change.